Practices of pica among pregnant women in a tertiary healthcare facility in Ghana - Kennedy Diema Konlan; Juliana Asibi Abdulai; Kennedy Dodam Konlan; Roberta Mensima Amoah; Abdul‐Razak Doat (Wiley, 2020)
Abstract Aim This study assessed the practice of pica among pregnant women in the Ho Teaching Hospital. Design Descriptive cross‐sectional. Methods Systematic sampling technique was used to recruit 286 pregnant women. Questionnaire was used to collect data. Data entered into Statistical Package for Social Sciences for analysis. Result Of the 286 pregnant women, 21.2% and 17.8% considered white clay and ice respectively as nutritious. Prevalence of pica was 47.5%, while 44.9% of pregnant women who practised pica reported they feel uncomfortable when they do not eat pica as 63.3% considered intake of pica as harmful. Among women who received education against pica practice, 49.4% have ever taken pica as 50.9% of them with education on effects of pica were currently engaged in the activity (χ2 = 1.93 p = .17). Conclusion Health professionals, especially midwives must intensify education on effects of pica among pregnant women.